Utopian Realism: The Struggle for Positive Peace in Frida Stéenhoff’s Stridbar ungdom (1907) - Mårsell, Maria (Nordic Theatre Studies, 2023)
Around the turn of the nineteenth century writer, and opinion leader, Frida Stéenhoff (1865–1945), developed a theory of the future and the present of society, and argued that contemporary ideas of the social, ethical, and aesthetical were provisional, not comparable to the coming. An affinity between drama and theory, as well as investigations of peace as an idea, are distinctive features of her writing. Her play, Stridbar ungdom / Pugnacious Youth (1907), can be positioned in a tradition of peace dramas spanning from Aristophanes’ Lysistrata to Sarah Kane’s Blasted. This article studies the utopian potential of peace in Pugnacious Youth. By reading the play with Ruth Levitas’ method the Imaginary Reconstitution of Society (IROS) – suggesting that utopia is a method rather than a goal in itself – peace does not emerge negatively, as non-war, but as concrete development and possible presence. Furthermore, the division between realism and idealism when it comes to militarism and peace, as well as the realist and idealist branches of the peace movement, are problematized. In conclusion, it appears that studying ideas of peace in fiction enables an alternative entry into the actualization of its not-yet-here quality.